PEMBENTUKAN KARAKTER SANTRI MELALUI PEMBIASAAN PEMBACAAN ASMAUL HUSNA - Aji, Singgih Prasetya; Azizah, Nur (DIDAKTIKA, 2021)
This study aims to describe and find out how students can form character through habituation of reading Asmaul Khusna at Madrasah Diniyah Salafiyyah Al Ittihad Al Barokah Karangude Kulon. The results showed that in the implementation of character building by habituation of reading Asmaul Khusna in Madrasah Diniyah Salafiyyah Al Ittihad Al Barokah Karanggude Kulon, namely in the process carried out before starting learning by using the habituation method, through this habituation process the students recited together, it is hoped that they can memorize seriously and be able to apply it with istiqomah so as to be able to form good personalities for the students. The impact obtained from character building through habituation of reading Asmaul Khusna in Madrasah Diniyah Salafiyyah Al Ittihad Al Barokah Karanggude Kulon is expected to be able to make students always remember God and be able to make students diligent, diligent and disciplined.Keywords: Character, Santri, Asmaul Husna